Improved kernelization and fixed-parameter algorithms for bicluster editing - Lafond, Manuel (Journal of combinatorial optimization, 2024)
Given a bipartite graph G , the Bicluster Editing problem asks for the minimum number of edges to insert or delete in G so that every connected component is a bicluster, i.e. a complete bipartite graph. This has several applications, including in bioinformatics and social network analysis. In this work, we study the parameterized complexity under the natural parameter k , which is the number of allowed modified edges. We first show that one can obtain a kernel with 4.5 k vertices, an improvement over the previously known quadratic kernel. We then propose an algorithm that runs in time O ∗ ( 2 . 581 k ) . Our algorithm has the advantage of being conceptually simple and should be easy to implement.